The economic burden of asthma prior to death: a nationwide descriptive study - Guilleminault, Laurent; Mounié, Michael; Sommet, Agnès; Camus, Claire; Didier, Alain; Reber, Laurent Lionel; Conte, Cécile; Costa, Nadège (Frontiers in Public Health, 2024)
Background In addition to the clinical burden, asthma is responsible for a high economic burden. However, little is known about the economic burden of asthma prior to death. Objective We performed an economic analysis to describe the costs during 12 and 24 months prior to asthma death between 2013 and 2017 in France. Methods An observational cohort study was established using the French national health insurance database. Direct medical and non-medical costs, as well as costs related to absence from the workplace, were included in the analysis. Results In total, 3,829 patients were included in the final analysis. Over 24 and 12 months prior to death, total medical costs per patient were €27,542 [26,545–28,641] and €16,815 [16,164–17,545], respectively. Total medical costs clearly increased over 24 months prior to death. Over 12 months prior to death, costs increased significantly according to age categories, with mean total costs of €8,592, €15,038, and €17,845, respectively, for the categories <18 years old, 18–75 years old, and 75+ years old (p < 0.0001). Over 12 months prior to death, costs were statistically higher in patients with a dispensation of six or more SABA canisters compared to those with a dispensation of five or less canisters (p < 0.0001). In multivariate analysis, comorbidities, hospital as location of death, and dispensation of 12 or more canisters of SABA per year are independent factors of the highest costs. Conclusion To conclude, the economic burden of asthma death is high and increases with time, age, and SABA dispensation.